Pain in Parkinson's disease: facts and uncertainties. (18th April 2018) - Antonini, A.; Tinazzi, M.; Abbruzzese, G.; Berardelli, A.; Chaudhuri, K. R.; Defazio, G.; Ferreira, J.; Martinez‐Martin, P.; Trenkwalder, C.; Rascol, O.
Abstract : Pain is one of the most common and troublesome non‐motor symptoms of Parkinson's disease (PD). It can appear at any time during the disease and is often present before diagnosis. However, there is little or no consensus on its definition. An expert group of clinicians with relevant research experience met to review the existing evidence and to identify gaps in our understanding leading towards AUTHOR: 'understanding towards' has been changed to 'understanding leading towards'. Please check and confirm that this is appropriate an optimized therapy of pain in PD. Key findings from epidemiologic, neurophysiologic, neuroimaging and clinical studies are reviewed. In each case, the evidence base is limited by wide variations in the definitions of pain applied, study methodologies and populations evaluated. Disease‐related and medical conditions trigger spontaneous pain in patients with PD, which is then abnormally processed and results in painful manifestations in specific body parts. Dopaminergic medications, such as rotigotine, as well as opiate analgesics, such as oxycodone, have shown positive results but future studies with more detailed pain characterization at inclusion are warranted.